Hubungan Metode Drill Terhadap Kemampuan Hitung Perkalian Siswa Kelas II di SDN Bareng 4 Jombang - Qomariyah, Elvy Nur Laillatul; Dwi Rochmania, Desty (Prodi Pendidikan Guru Sekolah Dasar, 2024)
This research aims to determine the effectiveness and relationship of the drill method to the multiplication calculation ability of class II students at SDN Bareng 4 Jombang. This research is quantitative research with an experimental type of research and uses a One Group Pre Test Post Test design. The sample used was class II students, totaling 10 students. The data collection method in this research uses tests and documentation. The test consists of 50 questions. The results of this research can be concluded that: (1) students' multiplication calculation abilities before applying the drill method are generally categorized as moderate with an average value of 63. (2) students' multiplication calculation abilities after applying the drill method are generally categorized as capable with an average value 91.6. (3) The relationship between the drill method and students' multiplication calculation skills shows that there is a significant relationship or influence. This can be seen from the t test significance value of 0.001 < 0.05, so H0 is rejected and H1 is accepted. This means that there is an influence between the independent variable and the dependent variable.